Paraganglioma periaórtico y efusión pericárdica en un perro Golden Retriever: Reporte de caso - Cortés R., Natalia (2024)
The case of a 10-year-old Golden Retriever dog treated at the ASMEVET veterinary hospital in the city of Tunja, Colombia is presented. The owner reported that the patient had an intermittent cough for 2 months. The physical examination revealed the patient to be hyperactive, body condition 4/5, and faint heart sounds. Echocardiography, chest x-ray, and electrocardiogram were performed, revealing pericardial effusion, increased size of the cardiac silhouette, and deviation of the S-T segment. Initially, treatment was attempted with antibiotics, diuretics and anti-inflammatory agents, without a favourable response. Two months later, it was necessary to perform emergency pericardiocentesis due to cardiac tamponade, and partial subphrenic pericardiectomy. Histopathological analysis revealed a paraganglioma. The patient survived 673 days after surgical treatment.